Molecular mechanism of benign biliary stricture inhibition by rosiglitazone-activated peroxisome proliferator-activated receptor gamma - Jiamei,Lu (2022)
SUMMARY OBJECTIVE: The aim of this study was to investigate whether rosiglitazone-activated peroxisome proliferator-activated receptor gamma can inhibit the occurrence of benign biliary stricture and further elucidate the relevant molecular signaling mechanism. METHODS: The primary cultured rat biliary fibroblasts following experiments were performed using within the fifth generation cells, which were separated from the bile ducts of Sprague-Dawley rats. The primary cultured rat biliary fibroblasts were co-cultured with 10 ng/mL transforming growth factor-beta 1 for stimulating collagen formation. Competent cells were transfected with siRNA that specifically target Smad3 or connective tissue growth factor to inhibit the expression of the corresponding proteins. The cells were incubated with 10 μmol/L rosiglitazone to activate peroxisome proliferator-activated receptor gamma. The cells were incubated with 10 μmol/L GW9662 in the pretreatment session to inactivate peroxisome proliferator-activated receptor gamma. ELISA was used to determine the levels of connective tissue growth factor and type I collagen in the cell supernatant. Western blotting was used to detect the levels of intracellular p-Smad3/t-Smad3. RESULTS: Rosiglitazone-activated peroxisome proliferator-activated receptor gamma inhibited the secretion of type I collagen induced by transforming growth factor-beta 1. Peroxisome proliferator-activated receptor gamma inhibitor GW9662 could significantly reverse the rosiglitazone-triggered inhibition of transforming growth factor-beta 1-induced type I collagen secretion by suppressing peroxisome proliferator-activated receptor gamma activation (p<0.01). Furthermore, we also found that the activation of peroxisome proliferator-activated receptor gamma was accompanied by the inhibition of transforming growth factor-beta 1-induced Smad3 phosphorylation (p<0.01), increased connective tissue growth factor expression (p<0.01), and production of type I collagen (p<0.01), all of which effects elicited by rosiglitazone could be reversed by peroxisome proliferator-activated receptor gamma inhibitor GW9662. CONCLUSION: Peroxisome proliferator-activated receptor gamma activated by rosiglitazone inhibits the transforming growth factor-beta1 -induced phosphorylation of Smad3 and the increased connective tissue growth factor expression as well as inhibits the secretion of type I collagen in biliary fibroblasts.